(untitled) (KULT_online, 2015)
With the reader Bildwissenschaft and Visual Culture, transcript publisher aims to provide a first “representative and commented edition” of crucial contributions to this specific field of research. Beyond its indisputable pragmatic value, however, the project is certainly not without its faults. Whether the canonizing effects live up to the dynamics of the still young discussion is doubtful, as this review contends.